Effects of Microbial Aerosol in Poultry House on Meat Ducks' Immune Function - Yu, Guanliu; Wang, Yao; Wang, Shouguo; Duan, Changmin; Wei, Liangmeng; Gao, Jing; Chai, Tongjie; Cai, Yumei (Frontiers in Microbiology, 2016)
The aim of this study was to evaluate effects of microbial aerosols on immune function of ducks and shed light on the establishment of microbial aerosol concentration standards for poultry. A total of 1800 1-d-old Cherry Valley ducks were randomly divided into 5 groups (A, B, C, D and E) with 360 ducks in each. To obtain objective data, each group had three replications. Concentrations of airborne bacteria, fungi, endotoxin in different groups were created by controlling ventilation and bedding cleaning frequency. Group A was the control group and hygienic conditions deteriorated progressively from group B to E. A 6-stage Andersen impactor was used to detect the aerosol concentration of aerobes, gram-negative bacteria, fungi and AGI-30 microbial air sampler detect the endotoxin, and Composite Gas Detector detect the noxious gas. In order to assess the immune function of meat ducks, immune indicators including H5 AIV antibody titer, IgG, IL-2, T-lymphocyte transformation rate, lysozyme and immune organ indexes were evaluated. Correlation coefficients were also calculated to evaluate the relationships among airborne bacteria, fungi, endotoxin and immune indicators. The results showed that the concentration of airborne aerobe, gram-negative bacteria, fungi, endotoxin have a strong correlation to H5 AIV antibody titer, IgG, IL-2, T-lymphocyte transformation rate, lysozyme and immune organ indexes, respectively. In addition, when the concentration of microbial aerosol reach the level of group D, serum IgG (6 - 8 weeks), lysozyme (4 week) were significantly higher than in group A (P < 0.05); serum IL-2 (7 and 8 weeks) , T-lymphocyte transformation rate, lysozyme (7 and 8 weeks), spleen index (6 and 8 weeks) and bursa index (8 week) were significantly lower than in group A(P < 0.05 or P < 0.01). The results indicated that a high level of microbial aerosol adversely affected the immune level of meat ducks. The microbial aerosol values in group D provide a basis for recommending upper limit concentrations of microbial aerosols for healthy meat ducks.